2019
DOI: 10.1161/str.50.suppl_1.6
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 6: Results From the DEFUSE 3 Trial: Good Leptomeningeal Collaterals Are Associated With Reduced Core Infarct Size but Not Improved Neurologic Outcome

Abstract: Introduction: The role of collaterals for acute ischemic stroke patients who qualify for endovascular thrombectomy (EVT) in the late therapeutic window (>6 hours from last known normal) remains unknown. We hypothesize that good collaterals on CT angiography (CTA) will moderate neurologic outcome and the effect of EVT. Methods: This is a prespecified analysis of DEFUSE 3. The primary outcome is functional independence (modified Rankin scale ≤2). Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…We found that poor baseline collateral status is associated with increased infarct growth between baseline and 24-h imaging. This finding is consistent with other studies that have examined the impact of collateral status on infarct growth in this time window (10). Secondly, we found that absence of reperfusion is associated with increased infarct growth beyond 24-h.…”
Section: Discussionsupporting
confidence: 93%
“…We found that poor baseline collateral status is associated with increased infarct growth between baseline and 24-h imaging. This finding is consistent with other studies that have examined the impact of collateral status on infarct growth in this time window (10). Secondly, we found that absence of reperfusion is associated with increased infarct growth beyond 24-h.…”
Section: Discussionsupporting
confidence: 93%
“…Patients with a robust filling of arteries distal to the site of occlusion on CTA are deemed to have favorable collaterals . However, analyses based on CTA imaging do not provide information as to how much blood flows into the ischaemic tissue and this limitation may partially explain the heterogeneous response of patients with favorable CTA collaterals to EMT and the finding that the CTA collateral score did not predict outcomes in late‐window thrombectomy patients selected for treatment by CT or MR perfusion imaging . Our results suggest that HIR and perfusion‐based measures of collateral flow might be superior to angiographic measures of collaterals in early as well as late time windows and future studies should test this hypothesis.…”
Section: Discussionmentioning
confidence: 79%
“…Second, this study cannot provide information on clinical outcomes after EVT according to the three different selection methods. In the DEFUSE-3 trial, pretreatment infarct core volumes of <70 mL (too large for inclusion according to the DAWN trial criteria) are associated with benefits for EVT, and good leptomeningeal collaterals on single-phase CT angiography were not predictive of outcomes [12,13]. Future studies are warranted to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%